Inovasi Dalam Kurikulum Pendidikan Islam untuk Meningkatkan Karakter dan Etika Siswa - Miswanto Miswanto; Abdul Halim (Journal on Education, 2023)
This study discusses the importance of innovation in the Islamic education curriculum to improve students' character and ethics. Innovation in Islamic education is a must in facing the various challenges faced by the younger generation in the modern era. By implementing innovation, Islamic education can become more relevant, interesting, and effective in shaping students' character and ethics. Some of the innovative approaches discussed in this study include a holistic approach in character and ethics learning, the integration of Islamic values ​​in every aspect of the curriculum, the use of technology in teaching ethics and morality, the use of Islamic digital applications and platforms, and experiential learning. Through the implementation of these innovations, it is hoped that students will be able to experience a fun, active, and in-depth learning experience about ethical values ​​in Islam. The conclusions show that innovation in the Islamic education curriculum is the key to forming a young generation who has good morals, has noble character, and is able to face various challenges in life with full confidence and moral awareness.